Political efficacy among Malaysian voters: the role of traditional and new media - Syed Abdullah Idid, Syed Arabi; Ahmed Dhaha, Ismail Sheikh Yusuf; Souket, Rizwanah (2014)
The technological advancement and political situations have dramatically impacted the way traditional and new media have played their role in society, especially in the political development of the country. The news on current affairs, politics and other social and economic aspects is made available to audience from many different media sources. Since scholars studied media, news media credibility has been a major concern to understand audience perceptions and attitudes towards the media and its role in politics. But little investigation has been conducted on news credibility as perceived by audience members. It is argued that trust in the media leads to trust in the political system and media would do well to instill confidence in the political efficacy among voters.. Scholars argue that media create agreement or disagreement among the audiences towards the political system. This study investigated media credibility among Malaysian voters by examining specifically the extent the voters trusted the traditional and new media. This study also examined how traditional and new media use and trust in the media explained the perceived political efficacy among the voters. Data were collected by administering the questionnaire on voters nationwide to understand their appreciation of media credibility and its contribution toward the political efficacy. The 2030 respondents were selected through quota-sampling from two parliamentary constituencies in each state. The data, collected in July 2012, were analyzed using SPSS version 17 for both descriptive and inferential statistics to answer the research objectives and test its hypotheses.